"I don't have options but to persevere." Experiences and practices of care for HIV and diabetes in rural Tanzania: a qualitative study of patients and family caregivers. Issue 1 (December 2016) - Mwangome, Mary; Geubbels, Eveline; Klatser, Paul; Dieleman, Marjolein
Abstract Background The high prevalence of chronic diseases in Tanzania is putting a strain on the already stretched health care services, patients and their families. This study sought to find out how health care for diabetes and HIV is perceived, practiced and experienced by patients and family caregivers, to inform strategies to improve continuity of care. Methods Thirty two in-depth interviews were conducted among 19 patients (10 HIV, 9 diabetes) and 13 family caregivers (6 HIV, 7 diabetes). Diabetes patients and caregivers were accessed through one referral facility. HIV patients and caregivers were accessed through HIV clinics at the district hospital, one health centre and one dispensary respectively. The innovative care for chronic conditions framework informed the study design. Data was analysed with the help of Nvivo 10. Results Three major themes emerged; preparedness and practices in care, health care at health facilities and community support in care for HIV and diabetes. In preparedness and practices, HIV patients and caregivers knew more about aspects of HIV than did diabetes patients and caregivers on diabetes aspects. Continued education on care for the conditions was better structured for HIV than diabetes. On care at facilities, HIV and diabetes patients reported that they appreciated familiarity with providers, warm reception, gentle correction of mistakes and privacy during care. HIV services were free of charge at all levels. Costs involved in seeking services resulted in some diabetes patients to not keep appointments. There was limited community support for care of diabetes patients. Community support for HIV care was through community health workers, patient groups, and village leaders. Conclusion Diabetes and HIV have socio-cultural and economic implications for patients and their families. The HIV programme is successfully using decentralization of health services, task shifting and CHWs to address these implications. For diabetes and NCDs, decentralization and task shifting are also important and, strengthening of community involvement is warranted for continuity of care and patient centeredness in care. While considering differences between HIV and diabetes, we have shown that Tanzania's rich experiences in community involvement in health can be leveraged for care and treatment of diabetes and other NCDs.